Discrete-time prey-predator model with Î¸-logistic growth for prey incorporating square root functional response - Santra, P.K. (Jambura Journal of Biomathematics (JJBM), 2020)
This article presents the dynamics of a discrete-time prey-predator system with square root functional response incorporating Î¸-logistic growth. This type of functional response is used to study the dynamics of the prey--predator system where the prey population exhibits herd behavior, i.e., the interaction between prey and predator occurs along the boundary of the population. The existence and stability of fixed points and Neimark-Sacker Bifurcation (NSB) are analyzed. The phase portraits, bifurcation diagrams and Lyapunov exponents are presented and analyzed for different parameters of the model. Numerical simulations show that the discrete model exhibits rich dynamics as the effect of Î¸-logistic growth.